Pediatric Meningoencephaloceles Endoscopic Endonasal Repair: Our Experience - Marfatia, Hetal K. (Allergy Rhinol (Providence), 2018)
BACKGROUND: Pediatric patients presenting with a nasal mass is uncommon and a high index of suspicion for it to be a meningoencephalocele is essential. Majority of these are congenital and require early intervention owing to the risk of meningitis. Surgery in these cases is very challenging because of the risk of anesthesia and limited space. OBJECTIVE: This study aimed to describe our technique and experience in managing pediatric meningoencephaloceles. METHODS: A retrospective study of 19 pediatric patients (age ranging from 40-day-old infants to 11.5-year-old children) was conducted at our tertiary care center from January 2012 to February 2017. Patients presenting with an intranasal meningoencephalocele were treated by endoscopic approach, using otological microinstruments. After detailed imaging and clinical evaluation, a tailored repair, using fat/fascia/cartilage, a multilayer closure, was carried out in all cases. RESULTS: All patients had a successful repair and recovery, except for one death following an episode of convulsion. There was a minor circumferential narrowing of the nasal vestibule and synechia formation in 2 of our cases. CONCLUSION: Transnasal endoscopic repair of meningoencephalocele is minimally invasive. It avoids permanent anosmia and is cosmetic. A combination of miniaturized instruments and a 4-mm 0° nasal endoscope gives excellent visual field and an adequate working space. Owing to the larger defects in congenital meningoencephaloceles, a multilayer repair provides excellent outcomes.